2021
DOI: 10.1001/jamahealthforum.2021.1615
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Processes of Care and Outcomes for Hospitalized General Medicine Patients Treated by Female vs Male Physicians

Abstract: IMPORTANCE Hospitalized medical patients cared for by female physicians may have decreased mortality rates compared with patients of male physicians. However, this association has yet to be assessed outside of the US, and little is known about factors that may explain this difference.OBJECTIVE To determine whether mortality, other hospital outcomes, and processes of care differed between the patients cared for by female and male physicians. DESIGN, SETTING, AND PARTICIPANTS This retrospective cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 70 publications
(134 reference statements)
0
8
1
Order By: Relevance
“…In our study, we identified an overall mortality rate of 7.8%, which is higher than what has been reported in other Canadian studies 5 14. One Canadian centre found that an institution-wide mortality of 3.3%, with 18.7% of cases reviewed having opportunities for improvements in care 5.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…In our study, we identified an overall mortality rate of 7.8%, which is higher than what has been reported in other Canadian studies 5 14. One Canadian centre found that an institution-wide mortality of 3.3%, with 18.7% of cases reviewed having opportunities for improvements in care 5.…”
Section: Discussioncontrasting
confidence: 50%
“…In Canada, GIM is a specialty that involves diagnosing and managing complex, polycomorbid, seriously ill patients suffering from advanced illness and/or diseases affecting more than one organ system. In-hospital mortality rates among hospitalised patients in Canada have been reported to range between 3.3 and 5% 5 14. Given that at an average-sized, urban, tertiary care centre in Canada, a GIM admitting service would be expected to have a per annum caseload of several thousand, conducting routine mortality reviews of all patient deaths would be a significant time commitment.…”
Section: Introductionmentioning
confidence: 99%
“…Recipients of weekly electronic table of 4 differences in hospital care and outcomes for general medical patients treated by female and male physicians in Ontario, Canada, 5 and the distribution of expenditures for insulin among various organizations in the pharmaceutical supply chain (Table ). 6 The wide reach of the JAMA Network has already been highly beneficial for JAMA Health Forum authors.…”
Section: Information Dissemination Datamentioning
confidence: 99%
“…During 2021, 844 manuscripts from authors in 31 countries were submitted to JAMA Health Forum , including 588 research manuscripts and 256 opinion manuscripts (Table). The manuscript acceptance rate was 21% overall and 18% for research manuscripts (Original Investigations, Research Letters, and Special Communications).…”
mentioning
confidence: 99%
“…Gender diversity can improve the quality of healthcare, as it provides a flexible workplace environment for both men and women and healthcare services with diverse values (12). Moreover, gender differences in healthcare delivery allow for more patient-centered communication (13), guideline adherence (14), and testing for patients by female doctors (15).…”
Section: Effects Of Diversity Promotionmentioning
confidence: 99%